Perancangan Website E-Commerce Dengan Pemanfaatan Framework Codeigniter Pada Di Chemistry Merch - Sukamto, Anton; Nurachmad, Edi; Mulyana, Ade; Arieswanto, Jenny; Danuputri, Chyquitha (FORMAT, 2025)
Facing extraordinary online-based trade in the current era requires information systems and information technology that are very adequate for the needs of suppliers, sellers or buyers. The same thing is faced by Chemistry Merch which operates in the online trading sector. Maximizing this technology is intended to facilitate interaction between companies and consumers. Apart from that, the product is widely known by the wider community and even throughout the world. Utilization of software in the form of PHP, Microsoft Visual Studio Code, Xampp and supported by the Codeigniter framework, UML and use case diagrams further clarifies procedures for selling and disseminating information in web form. The expected results start from design to input analysis, process analysis, output analysis and information technology architecture needs analysis, namely in the form of a web that contains the complete needs of consumers.